Exploring the Impact of Participation and Engagement on Confidence, Mediated by SDQ (Symptoms of Depression) - Savila, Zubia; Khoo Phaik Lin, Selina; Chong, Yong-Yee (International Journal of Sport Studies for Health, 2026)
Objective: This research aimed to examine how the level of participation and frequency of engagement influence symptoms of depression through sports confidence in the context of Pakistani athletes. Drawing on self-determination theory, particularly the need for competence, influences symptoms of depression via sports confidence.Methods & Materials: Based on SDT, the fulfillment of the need for competence (as reflected in sports confidence) is key to positive psychological outcomes. The participants were 357 athletes (125 females, 232 males), aged between 18-65 years old, who had been registered in competitions (national, international, university, college, and club-level) in Pakistan. The results were obtained using a partial least squares structural equation modelling (PLS-SEM) approach.Results: The results indicated that the level of participation significantly influences symptoms of depression. Furthermore, the frequency of engagement also influences symptoms of depression. However, depression has a significant mediating impact between frequency of engagement and level of participation with sports confidence. These results indicate the complexity of being involved in sport and athletes’ psychological well-being in relation to obtaining confidence in their abilities and their participation in sport.Conclusion: Building on these findings, further research is warranted to consider these relationships and the other psychological and contextual influences on athletes.